nab-Paclitaxel–Based Therapy in Underserved Patient Populations: The ABOUND.PS2 Study in Patients With NSCLC and a Performance Status of 2 - Gajra, Ajeet; Karim, Nagla Abdel; Mulford, Deborah A.; Villaruz, Liza Cosca; Matrana, Marc Ryan; Ali, Haythem Y.; Santos, Edgardo S.; Berry, Tymara; Ong, Teng Jin; Sanford, Alexandra; Amiri, Katayoun; Spigel, David R. (Frontiers in Oncology, 2018)
Introduction: The phase II ABOUND.PS2 study (NCT02289456) assessed safety/tolerability of a first-line modified nab-paclitaxel/carboplatin regimen for patients with advanced non-small cell lung cancer (NSCLC) and ECOG PS 2. Methods: Chemotherapy-naive patients with stage IIIB/IV NSCLC and ECOG PS 2 received 4 cycles of nab-paclitaxel 100 mg/m2 days 1 and 8 plus carboplatin AUC 5 day 1, q3w (induction). Patients without progression received nab-paclitaxel monotherapy (100 mg/m2 days 1 and 8 q3w) until progression/unacceptable toxicity. Primary endpoint: percentage of patients discontinuing induction due to treatment-emergent adverse events (TEAEs). Results: 11/40 treated patients (27.5%; 95% CI, 14.60-43.89) discontinued chemotherapy induction due to TEAEs; 16/40 (40.0%) continued nab-paclitaxel monotherapy. Median progression-free and overall survival were 4.4 (95% CI, 2.99-7.00) and 7.7 (95% CI, 4.93-13.17) months. Grade 3/4 TEAEs during induction included neutropenia (22.5%), anemia (17.5%), thrombocytopenia (5.0%), and peripheral neuropathy (2.5%). Conclusions: This nab-paclitaxel–based regimen was tolerable in patients with advanced NSCLC and ECOG PS 2, with efficacy comparable to historical chemotherapy data.